Estudio de estandarización con fines de automatización del proceso productivo de queso mozzarella en la planta CETTEPS-UNACH - Lomelin Bahamon, Diego Andres (2025)
This study aimed to analyze the standardization processes necessary to automate the mozzarella cheese production at the CETTEPS-UNACH manufacturing facility in Riobamba, Ecuador. A quantitative research approach was employed, utilizing direct observation, surveys, and priority matrices to identify critical stages and potential improvements within the production process. The study is descriptive, offering a detailed analysis of the manufacturing process, from milk reception to cheese packaging. The findings highlight key stages with high automation potential, such as pasteurization (8.92), followed by the washing and stretching process (8.12), and cooling (7.92). These phases were characterized by high levels of standardization, well-defined protocols, and suitable equipment, indicating the feasibility of automation implementation. Conversely, stages like milk reception and the addition of calcium and rennet scored low due to a lack of standardization and the absence of proper automation equipment. Based on this analysis, the pasteurization process was identified as the most suitable candidate for automation. This decision is grounded in its high standardization, availability of compatible equipment, and its significant impact on cheese quality. The proposed automation involves the adoption of an HTST system tailored to the production scale, which would enhance milk safety and mozzarella cheese quality. In conclusion, this study found that the mozzarella cheese manufacturing process at CETTEPS UNACH is at an intermediate level of standardization, with an overall quality score of 52.5%. This study suggests that implementing automation, particularly in the pasteurization stage, will improve product consistency and provide valuable learning opportunities for students in the Agro-industrial Engineering program.